PENERAPAN MAQASHID SHARIAH TERHADAP GOOD CORPORATE GOVERNANCE PADA HOME INDUSTRY - Retno Amelia budi; Mohamad Djasuli (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
Home industry is a place for the majority of people who are able to grow and develop independently by contributing greatly and occupying a strategic role in economic development. In addition, home industry is also a business activity that is able to expand employment opportunities and provide broad economic services to the community, and can play a role in improving the economy, but based on observations and existing temporary data, the existence of home industry has not been able to maximize welfare based on indicators of welfare according to BKKBN, which include indicators of income, expenditure consumption, housing, education, and health. This paper aims to explain the ethics of production within the framework of maqashid sharia which consists of the maintenance of five basic human needs, namely the maintenance of religion, soul, mind, lineage, and property. The approach used in this paper is the maqashid sharia approach. This paper aims to explain the ethics of production within the maqashid sharia framework which consists of maintaining five basic human needs, namely the maintenance of religion, soul, mind, lineage, and property. The approach used in this paper is the maqashid sharia approach